Pemanfaatan Lactobacillus Plantarum 1 RN2-12112 dalam Pembuatan Minuman Sinbiotik Berbasis Sari Umbi Bengkuang dan Naga Merah - Rani Fadilah Fajri; Yusmarini Yusmarini; Usman Pato (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2021)
This research was conducted to obtain the best concentration of starter Lactobacillus plantarum 1 RN2-12112 in the manufacture of synbiotic drinks based on yam and red dragon juice. The study used a completely randomized design (CRD) with 5 treatments and 3 replications. The treatments were BN1 (2%), BN2 (3%), BN3 (4%), BN4 (5%) and BN5 (6%). The data obtained were analyzed statistically using analysis of variance (ANOVA) and followed by Duncan's multiple range test (DMRT) at the 5% level. The results showed that different starter concentrations had a significant effect on lactic acid bacteria, total acidity titration (pH), descriptive assessment of aroma, taste, viscosity and hedonic sensory but no significant effect on descriptive color assessment. The best treatment in this study was BN2 (3% starter concentration) which produced a synbiotic drink with a pH value of 3.86, a total lactic acid of 1.05% and a total LAB of 9.18 CFU/ml with a characteristic reddish-purple color, a characteristic fermented flavour, a slightly sour taste. acid and overall preferred by the panelists.Keywords :Lactobacillus plantarum, red dragon, yam tuber